First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Exploring the potential of theory-based evaluation to strengthen marine spatial planning practice - Rachel Zuercher; Nicole Motzer; Natalie C. Ban; Wesley Flannery; Anne D. Guerry; Rafael A. Magris; Shauna L. Mahajan; Ana K. Spalding; Vanessa Stelzenmüller; Jonathan G. Kramer (Ocean & Coastal Management, 2023)

The Role of Eelgrass in Marine Community Interactions and Ecosystem Services: Results from Ecosystem-Scale Food Web Models - Mark L. Plummer; Chris J. Harvey; Leif E. Anderson; Anne D. Guerry; Mary H. Ruckelshaus (Ecosystems, 2013)

Review - James G. Gosselink; Guerry O. Holm; L. Katherine Kirkman; Charles E. Sasser; Christopher Craft (Wetlands, 2002)

Amphibian Distributions in a Landscape of Forests and Agriculture: an Examination of Landscape Composition and Conf iguration - Anne D. Guerry; Malcolm L. Hunter (Conservation Biology, 2002)
Landscapes can be described by two essential features: the composition and spatial arrangement of patches. We considered the roles of these basic landscape descriptors by examining how the occurrence of nine amphibian species in breeding ponds was associated with the area of forested habitat and the proximity of ponds to forested habitat. We used visual and call surveys to compare the composition of amphibian assemblages in 116 ponds adjacent to or separated from forest and surrounded by different amounts of forested land. The area of forest and pond adjacency to forest were not associated ( t = −0.13, n isolated = 64, n connected = 52, p = 0.21), which means these factors can manifest their effects separately. We used logistic regression to test predictions about associations between each species and forest area and to test for associations with pond‐forest adjacency. Seven of nine species were associated with forest area. Wood frogs ( Rana sylvatica ), green frogs ( Rana clamitans ), eastern newts ( Notopthalmus viridescens ), spotted salamanders ( Ambystoma maculatum ), and salamanders of the blue‐spotted/Jefferson's complex ( Ambystoma laterale/A. jeffersonianum ) were more likely to occupy ponds in more forested areas, whereas leopard frogs ( Rana pipiens ) and American toads ( Bufo americanus ) were negatively associated with forest area. Three species were associated with pond‐forest adjacency. Spotted salamanders and salamanders of the blue‐spotted/Jefferson's complex were more likely to occupy ponds that were adjacent to forest. In areas with little forest, leopard frogs were more likely to occur in adjacent ponds, but the reverse was true for areas with extensive forests. Our results suggest that the composition of the landscape surrounding breeding ponds is associated with the likelihood of occurrence of most of the species examined and that landscape configuration is also important for a smaller subset of species.